The Development of Qurlanic Interpretation in the Era of Reforrnation in Indonesia - Muhammad Arifin (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Hasil Penitaian Peer Review The Development of Qurlanic Interpretation in the Era of Reforrnation in Indonesia